Identifying the presence of subsurface oxygen on the Ti3C2 MXene using H2O as a probe molecule: a DFT study - Gouveia, José D. (2024)
Oxycarbide MXenes are two-dimensional transition metal carbides with subsurface oxygen content within their carbon layers. Substitutional oxygen atoms are thermodynamically very stable, impose virtually no lattice strain on their surroundings, and do not change the metallic behaviour of Ti3C2, making them very difficult to detect experimentally. Here, water is suggested as a probe to identify subsurface oxygen atoms on the H2-exposed and heat pre-treated Ti3C2 MXene. Independently of the oxygen concentration, density functional theory calculations show that water can adsorb near subsurface oxygen atoms as well as on stoichiometric Ti3C2 regions of the material and is deemed appropriate for identifying substitutional oxygen defects on Ti3C2 through frequency analysis. The calculated stretching mode of water increases by at least 67 cm1 in the presence of subsurface oxygen, allowing the experimental detection of this defect, even at the lowest concentration considered, i.e., a replacement of 3 % of carbon by oxygen atoms.